Fast accrual of C and N in soil organic matter fractions following post-mining reclamation across the USA. (1st March 2018) - Angst, Gerrit; Mueller, Carsten W.; Angst, Šárka; Pivokonský, Martin; Franklin, Jennifer; Stahl, Peter D.; Frouz, Jan
Abstract: Reclamation of post-mining sites commonly results in rapid accrual of carbon (C) and nitrogen (N) contents due to increasing plant inputs over time. However, little information is available on the distribution of C and N contents with respect to differently stabilized soil organic matter (SOM) fractions during succession or as a result of different reclamation practice. Hence, it remains widely unknown how stable or labile these newly formed C and N pools are. Gaining a deeper understanding of the state of these pools may provide important implications for reclamation practices with respect to C sequestration. We thus investigated C, N, and plant-derived compounds in bulk soil and SOM fractions during succession in post-mining chronosequences (reclaimed with overburden or salvaged topsoil) located along a northwest to southeast transect across the USA. Our results indicate that current reclamation practices perform well with respect to rapid recovery of soil aggregates and the partitioning of C and N to different SOM fractions, these measures being similar to those of natural climax vegetation sites already 2–5 years after reclamation. A general applicability of our results to other post-mining sites with similar reclamation practices may be inferred from the fact that the observed patterns were consistent along the investigated transect, covering different climates and vegetation across the USA. However, regarding SOM stability, the use of salvaged topsoil may be beneficial as compared to that of overburden material because C and N in the fraction regarded as most stable was by 26 and 35% lower at sites restored with overburden as compared to those restored with salvaged topsoil. Plant-derived compounds appeared to be mainly related to bio-available particulate organic matter and particulate organic matter partly stabilized within aggregates, challenging the long-term persistence of plant input C in post-mining soils. Graphical abstract: Image 1 Highlights: C, N, and plant lipids were studied in bulk soil and fractions in chronosequences. Allocation of C and N to fractions was similar to climax sites after 2–5 yrs. The soils' ability to accumulate, stabilize, and store C rapidly recovered. Sites with salvaged soil had more stabilized C (and N) than sites with overburden.